Surveillance and charitable donation behaviour : a social marketing approach - Karen White; Sanjaya Gaur; Sheau-Fen Yap; Wee Yu Ghee (Faculty of Entrepreneurship and Business,UMK, 2015)
With the focus of the media headlines on the economic and political impacts, it is unclear to what extent this has affected charitable donations. The successful implementation of a donation campaign represents a major marketing challenge in the current economic climate. There is a growing consensus that social marketing can play an important role in persuading charitable donation behaviour. Our study addresses this salient research question from a social marketing perspective: What are the motivators of charitable donation behaviour? While we acknowledge that a variety of factors may affect consumer charitable behaviour, we focus on providing a conceptual understanding of how the effect of surveillance on charitable donation behaviour could be intervened by personality factors such as self-monitoring and need for approval. Ultimately, we seek to improve our understanding of consumer engagement in charitable donation behaviour from a social marketing perspective, in turn, consumer welfare.